Combination of 3D Printing and Electrospinning Techniques for Biofabrication (Adv. Mater. Technol. 7/2022). Issue 7 (12th July 2022) - Yang, Dan‐Lei; Faraz, Fazal; Wang, Jie‐Xin; Radacsi, Norbert
Abstract : Biofabrication In article number 2101309, Norbert Radacsi and co‐workers show that the combination of electrospinning with 3D printing can create scaffolds suitable for cell growth. The electrospun nanofibers help to attract cells due to their extracellular matrix‐like structure, while the 3D‐printed parts can serve as macroscopic structure material.